Influence of perforation and sound-absorbing material filling on acoustic attenuation performance of three-pass perforated mufflers. (January 2018) - Huang, Hongpu; Ji, Zhenlin; Li, Zhuoliang
The finite element method is employed to calculate the transmission loss of three-pass perforated reactive and hybrid mufflers. The effects of perforated tubes and bulkheads on the transmission loss of three-pass reactive mufflers are investigated numerically. Two types of hybrid mufflers are considered, and the effects of sound-absorbing material filling and packed outlet tube on the acoustic attenuation performance of mufflers are analyzed. The perforations of the tubes and bulkheads and sound-absorbing material filling are demonstrated to have significant influence on the acoustic attenuation behaviors of the mufflers. The perforation of the tubes and bulkheads may shift the resonance from the low- to middle-frequency range. The sound-absorbing material filling in the middle chamber improves the acoustic attenuation performance at middle to higher frequencies and provides a relatively flat and broadband acoustic attenuation. It is found that the solid inlet or outlet tube replacing the perforated tube and sound-absorbing material filling in the middle chamber increases the pressure drops, while the rest configurations change the pressure drops slightly.